Chapter Postverbal subjects and nuclear pitch accent in Italian wh-questions - Bocci, Giuliano (De Gruyter, 2018)
The structure of this chapter is as follows. We first illustrate the phenomenon of subject inversion in Italian wh-questions (§ 2). In Section 3, we present the results of a syntactic experiment on the distribution of subjects in the embed-ded clause of wh-questions. Our analysis is presented in Section 4, where we directly relate the syntactic and prosodic peculiarities of Italian wh-questions to the successive cyclic nature and to the intermediate positions of wh-movement. We show that while subject inversion is a phenomenon that involves the edge of the C-phrase, the assignment of NPA additionally involves the vP-edge. We then attempt to capture the observed patterns and to provide further support to our analysis by comparing direct and indirect wh-questions with respect to both subject inversion and their prosodic properties (§ 5). A summary and some final remarks close the chapter.